P513 Prospective study on patients' satisfaction and impact on quality of life of corticosteroid therapy in patients with Inflammatory Bowel Disease. (30th January 2023) - Navarro Llavat, M; García-Bosch, O; Castro-Poceiro, J; Bargalló García, A; Ruiz Arroyo, D; Navas Bravo, Y; Erice Muñoz, E; Barquero Declara, D; Mata Bilbao, A; Martín Llahí, M; Ariza Solé, X; Hernández Ballesteros, C; et al.
Abstract: Background: Corticosteroids (Cs) remain the first-line therapy for moderate-to-severe flares in patients with inflammatory bowel disease (IBD), both Crohn's disease (CD) and ulcerative colitis (UC). On the other hand, their use has been associated to multiple adverse events (AEs) in randomized controlled trials and registries. Nevertheless, recent studies have repeatedly observed that the use of Cs has not decreased in spite of the increasing availability of biological agents and new small molecules licensed for IBD. The impact of Cs therapy on patients' quality of life (QoL) and the patients' perception on Cs have not been properly assessed in IBD. The purpose of this study was to assess the impact of a standard Cs course on the patients' QoL and their satisfaction with treatment. Methods: A prospective, longitudinal and observational study was conducted in adult IBD. All subjects received the same standard Cs regimen: starting dose of 1mg/kg/day (maximum 60mg/day) and tapering after 14 days with 10mg per week until reach 20mg/day, thereafter reduction was 5mg per week. QoL was assessed by the IBDQ-9 questionnaire at baseline, week 4 and at the end of Cs. Treatment satisfaction was assessed by the TSQM1.4 questionnaire at week 4 and at the end of Cs. Results: Sixty-three patients were included in the study (54% CD and 43% UC; mean age 38.5±14.9 years; 46%females). Cs therapy failed in 41% of cases (active disease upon Cs discontinuation or need for rescue therapy). AEs attributable to Cs were reported in 84.1%, the most frequent were dermatologic (acne and moon face) (60.3%), hypokalemia (44.8%) and poor quality of sleep (40%). Serious AEs were reported in 20, 6%, mostly mild or moderate infections that resolved without sequelae. IBDQ-9 scores increased 12.4 and 13.5 points at 4 weeks and at the end of Cs, respectively ( p <0.05). Improvement in QoL was not associated with any of the analysed factors (gender, age, type of IBD, response to treatment and AEs). The overall degree of satisfaction with Cs was 68.5 over 100 points, with the highest score related to satisfaction with adverse events (82/100). Satisfaction with treatment was only associated with the achievement of clinical remission or development of steroid dependence. Conclusion: A standard Cs course significantly increases the QoL of patients with IBD. Furthermore, a high satisfaction with treatment was perceived by patients.